Conversion of diffusely abnormal white matter to focal lesions is linked to progression in secondary progressive multiple sclerosis. (February 2021) - Dadar, Mahsa; Narayanan, Sridar; Arnold, Douglas L; Collins, D Louis; Maranzano, Josefina
Background: Diffusely abnormal white matter (DAWM) regions are observed in magnetic resonance images of secondary progressive multiple sclerosis (SPMS) patients. However, their role in clinical progression is still not established. Objectives: To characterize the longitudinal volumetric and intensity evolution of DAWM and focal white matter lesions (FWML) and assess their associations with clinical outcomes and progression in SPMS. Methods: Data include 589 SPMS participants followed up for 3 years (3951 time points). FWML and DAWM were automatically segmented. Screening DAWM volumes that transformed into FWML at the last visit (DAWM-to-FWML) and normalized T1-weighted intensities (indicating severity of damage) in those voxels were calculated. Results: FWML volume increased and DAWM volume decreased with an increase in disease duration ( p  < 0.001). The Expanded Disability Status Scale (EDSS) was positively associated with FWML volumes ( p  = 0.002), but not with DAWM. DAWM-to-FWML volume was higher in patients who progressed (2.75 cm 3 vs. 1.70 cm 3 ; p  < 0.0001). Normalized T1-weighted intensity of DAWM-to-FWML was negatively associated with progression ( p  < 0.00001). Conclusion: DAWM transformed into FWML over time, and this transformation was associated with clinical progression. DAWM-to-FWML voxels had greater normalized T1-weighted intensity decrease over time, in keeping with relatively greater tissue damage. Evaluation of DAWM in progressive multiple sclerosis provides a useful measure for therapies aiming to protect this at-risk tissue with the potential to slow progression.